Integrating virtual reality and haptics for renal puncture surgical simulator - Yonghang Tai; Lei Wei; Hailing Zhou; Nahavandi, Saeid; Junsheng Shi; Qiong Li (2016 2nd IEEE International Conference on Computer and Communications (ICCC), 2016)
Percutaneous nephrolithotomy is one of the most effective and invasive surgeries in renal calculi therapies. Traditional puncture training simulation is conducted by animals' organs or bench models which does not represent neither visual nor tactile clues through the actual procedure. In addition, the accuracy of the training results is also debatable due to the artificial setup. In this paper, we propose a haptically-enabled virtual reality (VR) renal puncture simulation system, which utilises a novel force model specifically for trocar needle puncture on multi-layered kidney (capsule, cortex and pyramid) simulation. The system is applied to substitute the conventional renal puncture vocational training for novice urologists. 18G trocar needle with 20 cm length punctured force feedback model is employed to evaluate the haptic rendering, where both damping force and dynamic friction force model are accurately simulated. A detailed human kidney anatomical structure reconstructed from CT images is also implemented for realistic visual and haptic rendering. The proposed virtual training simulation environment can also be implemented to simulate other kidney-related puncture training and evaluation.